Altered Cerebral Blood Flow in Alzheimer's Disease With Depression - Li, Runzhi; Zhang, Yanling; Zhuo, Zhizheng; Wang, Yanli; Jia, Ziyan; Sun, Mengfan; Zhang, Yuan; Li, Wenyi; Duan, Yunyun; Yao, Zeshan; Weng, Haoyi; Wei, Juan; et al. (Frontiers in Psychiatry, 2021)
Background: Depression is common in Alzheimer’s disease (AD) with an unclear neural mechanism. This study aimed to investigate the underlying cerebral perfusion associated with depression in AD and evaluate its clinical significance. Method: Twenty-one AD patients and 21 healthy controls (HCs) were enrolled in this study. The depressive symptom was defined according to Hamilton Depression Rating Scale (HAMD). Nine patients were diagnosed as AD with depression symptoms (HAMD>7). Three-dimensional pseudo-continuous arterial spin labeling MR imaging was conducted to measure regional cerebral blood flow (CBF). Neuropsychological tests covered cognition and depressive scores. Between groups comparisons on clinical variables and regional CBFs, relationship between regional CBF and depressive score, and identification of AD patients with depression were performed using covariance analysis, linear regression and receiver operating characteristic (ROC) analysis respectively. Results: Compared to HCs, AD patients without depression exhibited lower gray matter CBF (p=0.016); Compared to AD without depression, AD patients with depression had higher CBF in the right supplementary motor area (39.23 vs 47.91 ml/100 g/min, p=0.017) and right supramarginal gyrus (35.54 vs 43.85 ml/100 g/min, p=0.034). CBF in the right supplementary motor area was correlated with depressive score (β=0.46, p=0.025). The combination of CBF in right supplementary motor area, supramarginal gyrus and age could identify AD with depression from those without depression with a specificity of 100%, sensitivity of 66.67%, accuracy of 85.71%, area under the curve of 0.87. Conclusions: Our findings suggested that hyperperfusion of the right supplementary motor area and right supramarginal gyrus were associated with depression syndrome in AD, which could provide a potential neuroimaging marker to evaluate the depression state in AD.